2020
DOI: 10.1038/s41467-020-17355-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging spatiotemporal evolution of molecules and active sites in zeolite catalyst during methanol-to-olefins reaction

Abstract: Direct visualization of spatiotemporal evolution of molecules and active sites during chemical transformation in individual catalyst crystal will accelerate the intuitive understanding of heterogeneous catalysis. So far, widespread imaging techniques can only provide limited information either with large probe molecules or in model catalyst of large size, which are beyond the interests of industrial catalysis. Herein, we demonstrate a feasible deep data approach via synergy of multiscale reaction-diffusion sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 62 publications
2
62
0
Order By: Relevance
“…Structured illumination microscopy (SIM) was used to resolve the location of carbonaceous species for ZEOL samples. According to the previous experimental work 46 48 and theorical calculations 49 51 , the excitation wavelengths of B n + , N n + , PH n + , and PYR n + are situated around 390, 480, 560, and 640 nm, respectively, and the corresponding emission wavelengths are located in the range of 480–490, 500–520, 620–630, and 670–700 nm, respectively. The wavelengths of illumination and emission detection of SIM used in this work are 405 (detection at 435–485 nm), 488 (detection at 500–545 nm), 561 (detection at 570–640 nm), and 640 nm (detection at 663–738 nm), respectively, which can cover the characteristic area of excitation and emission wavelengths of B n + , N n + , PH n + , and PYR n + .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Structured illumination microscopy (SIM) was used to resolve the location of carbonaceous species for ZEOL samples. According to the previous experimental work 46 48 and theorical calculations 49 51 , the excitation wavelengths of B n + , N n + , PH n + , and PYR n + are situated around 390, 480, 560, and 640 nm, respectively, and the corresponding emission wavelengths are located in the range of 480–490, 500–520, 620–630, and 670–700 nm, respectively. The wavelengths of illumination and emission detection of SIM used in this work are 405 (detection at 435–485 nm), 488 (detection at 500–545 nm), 561 (detection at 570–640 nm), and 640 nm (detection at 663–738 nm), respectively, which can cover the characteristic area of excitation and emission wavelengths of B n + , N n + , PH n + , and PYR n + .…”
Section: Resultsmentioning
confidence: 77%
“…The interatomic interactions were described by the condensed-phase-optimized molecular potentials for atomistic simulation studies (COMPASS) force field. The applicability of the used force field was checked in the previous work 51 . The Ewald & Group summation method has an Ewald accuracy of 10 −5 kcal mol −1 when it is used for calculating electrostatic potential energy.…”
Section: Methodsmentioning
confidence: 99%
“…Gao et al. [ 79 ] developed a deep data method by coupling multiscale reaction‐diffusion simulations and super‐resolution structured illumination microscopy to explore the characteristics of the SAPO‐34 catalyzed methanol‐to‐olefins reactions. This method realizes the direct visualization of the spatiotemporal evolution of molecules (including coke) and active sites in a micrometer‐sized crystal, while conventional imaging techniques can only provide limited information with probe molecules or catalysts of large size.…”
Section: Nature‐inspired Optimization Of Hierarchical Catalystsmentioning
confidence: 99%
“…Other research works have demonstrated the formation of larger (and insoluble) polycyclic aromatics in small-pore catalysts, which have been hypothesized to be on the external surface of the crystal [25] or forming cross-cavity polycyclic aromatic species at the edge of the crystal. [42] In two recent works from Liu and co-workers, [43,44] the nature of the coke species have been revealed using Fourier transformed ion cyclotron resonance (FT-ICR/MS). These works indicate, for the first time, that coke growths in SAPO-18 or -34 following a cage-passing mechanism, cross-linking multicore aromatics.…”
Section: Introductionmentioning
confidence: 99%